Site-Seeing: Rome’s Queen Catacomb - Sauter, Megan (The Biblical archaeology review, 2023)
A short walk through Rome confirms the richness of its history. From the Pantheon to the Colosseum, the city boasts magnificent architecture and art. Yet it might surprise that some of the city’s most significant art lies beneath its surface. Rome has more than 40 catacombs scattered around its ancient perimeter, often along major roads, […]